2021
DOI: 10.3390/molecules26051440
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization, Biocompatibility and Antifungal Efficacy of a Denture-Lining Material Containing Cnidium officinale Extracts

Abstract: Herein, we investigated the surface characterization and biocompatibility of a denture-lining material containing Cnidium officinale extracts and its antifungal efficacy against Candida albicans. To achieve this, a denture-lining material containing various concentrations of C. officinale extract and a control group without C. officinale extract were prepared. The surface characterization and biocompatibility of the samples were investigated. In addition, the antifungal efficacy of the samples on C. albicans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Plaque and bacterial adhesion affect the discoloration of restorations, denture stomatitis, and general health [ 3 , 18 ]. Inhibiting the microbiome prevents denture stomatitis; however, the denture base does not have antifungal properties [ 1 ]. Ideally, dentures should exhibit stable color and surface properties without irritation of the oral mucosa [ 4 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plaque and bacterial adhesion affect the discoloration of restorations, denture stomatitis, and general health [ 3 , 18 ]. Inhibiting the microbiome prevents denture stomatitis; however, the denture base does not have antifungal properties [ 1 ]. Ideally, dentures should exhibit stable color and surface properties without irritation of the oral mucosa [ 4 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…When surface hardness is low, the surface can be easily deformed. It has been shown that the denture surface is affected when cleaning dentures; mechanical cleaning techniques and denture cleansing agents adversely affect the surface by increasing wear and decreasing the stability of dental prostheses [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations